Risk Factors Analysis for Gastroesophageal Reflux Disease in COVID-19 Pandemic Era on Resident Physicians Faculty of Medicine Brawijaya University - Sakti, Pandu Tridana; Mustika, Syifa (Jurnal Penyakit Dalam Indonesia, 2022)
Introduction. Resident physicians have a high risk of GERD due to excessive fatigue especially during a COVID-19 pandemic. However, research on resident physicians risk factors for the incidence of GERD in the COVID-19 pandemic era has never been conducted. This study aimed to analyze the risk factors for GERD in the era of the COVID-19 pandemic on resident physicians. Methods. This study used an analytic observational design with a cross sectional approach. Subjects were resident physicians in clinical and pre-clinical stage at the Faculty of Medicine Brawijaya University which were selected using random sampling method. Questionnaires were given to subjects using google forms, consisted of education burden, diet, psychosocial-economic, and GERDQ quiestionnaire. Risk factor analysis was performed using chi-square and logistic regression with a significance level of p Results. Out of 230 subjects, most of them were female (54.5%) and mean of age was 30.32 (SD 2.60) years. The risk factors for GERD in resident physicians at Brawijaya University are hypertension (p=0.035), smoking (p=0.019), educational burden [total working hours ≥40 hours/week (p Conclusion. Education burden, diet, and psychosocial-economic factors are associated with the incidence of GERD in resident physicians in the pandemic era.